Lethal Means Assessment and Counseling in the Emergency Department: Differences by Provider Type and Personal Home Firearms. Issue 5 (29th June 2020) - Diurba, Sofiya; Johnson, Rachel L.; Siry, Bonnie J.; Knoepke, Christopher E.; Suresh, Krithika; Simpson, Scott A.; Azrael, Deborah; Ranney, Megan L.; Wintemute, Garen J; Betz, Marian E.
Abstract : Objective: This study examined emergency department (ED) and behavioral health (BH) provider attitudes and behaviors related to lethal means screening and counseling of patients with suicide risk, specifically examining differences by provider type and whether providers had firearms in their own home. Methods: Emergency department providers (physicians and mid‐level practitioners) and behavioral health (BH) providers at four Colorado EDs completed an anonymous, web‐based survey. Results: Fewer ED providers (35%) than BH providers (81%) felt confident in their ability to counsel patients about lethal means ( p < .001). In multivariable analysis, the only clinical or provider factor associated with often or almost always asking patients about firearm access was provider type, with BH providers more likely than ED providers to ask in all scenarios (OR: 5.58, 95% CI 1.68–18.6). Behaviors and attitudes about lethal means counseling did not vary by whether the provider had firearms at home. Almost all providers said that additional training and protocols about how to help patients make firearm storage decisions would be helpful. Conclusions: Gaps in ED‐delivered lethal means counseling persist, highlighting directions for future provider education and protocol development.